The values of satisfying the inequality above range from where .
Find .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f ( x ) = ⎩ ⎪ ⎪ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎪ ⎪ ⎧ ( x − 1 ) − 1 ( x − 2 ) − 2 ( x − 1 ) − 1 − ( x − 2 ) − 2 − ( x − 1 ) − 1 − ( x − 2 ) − 2 ∀ x ≥ 2 ∀ 1 ≤ x < 2 ∀ x < 1
Case 1:-
x − 2 x − 4 ⟹ x ≤ 0 ∈ ( 2 , 4 ]
Case 2:-
x − 2 x ≥ 0 ⟹ x Bute this equation ia true only ∀ 1 ≤ x < 2 ∴ x ∈ ( − ∞ , 0 ] ∪ ( 2 , ∞ ) ∈ ϕ
Case 3:-
x x ⟹ 1 ⟹ x ≤ 0 ≥ 0 , x = 0 ∈ ϕ
Therefore the final solution set is ( 2 , 4 ] .
Thus, a + b = 2 + 4 = 6 .